Analisis Kualitas Pelayanan Pada pelayanan Pendaftaran Dan Pengurusan Perkara Di Pengadilan Tata Usaha Negara Mataram - Abdur rahman; Nurul Hidayati Indra Ningsih; Oktriliani Gelora Jehadianti (Universitas Muhammadiyah Mataram, 2019)
This study aims to find out Service Quality in Case Registration and Management Services at Mataram. State Administrative Court Supporting factors and inhibitors of Service Quality in Case Registration and Management Services at the Mataram State Administrative Court. The method of this research is descriptive research with a qualitative approach. Qualitative descriptive research is a study that aims to describe and describe events and phenomena that occur in the field and present data in a systematic, factual, and accurate manner regarding the facts or phenomena that occur in the field. Data collection is done by Observation, Interview, and Documentation Techniques. The researcher used source triangulation to check the validity of the research data. Data analysis in this study uses three components consisting of data reduction, data presentation, and conclusion drawing. The results of this study indicate that Service Quality at the Case Registration and Management Service at the Mataram State Administrative Court has implemented the dimensions of Simplicity, Clarity, Accuracy, Transparency, Facilities & Infrastructure, Ease of Access, Discipline and Comfort along with indicators. The inhibiting factor for the case registration and management services at the Mataram State Administrative Court is the lack of employee resources and the lack of supporting infrastructure in Panitra Muda Space Case. While the supporting factors are friendliness in serving the community, the enthusiasm given by employees to each other, holding a coordination meeting or some kind of evaluation every three months then giving awareness to serving the community sincerely and in accordance with conscience. Another supporting factor is the existence of facilities in the form of tools to facilitate the service process.